STUDI KUALITAS AIR SUNGAI TELAGA WAJA KABUPATEN KARANGASEM - K.G. Darma Susila; I.W. Sandi Adnyana; I.W. Budiarsa Suyasa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Telaga Waja River in Karangasem Regency has got water discharge from 2.500 to 3.500 litre per second. The use of fertilizer, farm and household cesspool disposal, and changes of land function can reduce the quality of the water. This research is done in order to know the quality of water and index of its pollution. This research is done in Telaga Waja river for along 10 kilometres from Besakih Village to Muncan Village from August until November 2011. The research of physic parachmeter, chemistry and microbiology by taking sample for insitu and eksitu examination are compared with the standard quality of Balinese Goverment Regulation No.8/2007. While the observation and interview are done in order to know beha,1our of the people in polluting the water. Result of the research shows that the concentration of Fecal coli and Total coliforms reach 240.000.000 MPN/100 ml It is more than standard quality of all classes.The analysis of COD is more than first class water quality, BOD and Fosfat are more than third class water quality and DO concentration is less than minimum first class water concentration. The evaluation of Pollution Index (Pl) for first class water in all location is high polluted. Evaluations PI of third and fou1th class standard water quality in Menanga Village and Muncan Village are medium polluted and from Rendang Village until Muncan Village is high polluted in the delta of the river. Water condition indicate function ofTelaga Waja watershed for agriculture, living place, tourism ( rafting, restaurant, and villa), and mining pollute the water. Base on the evaluation of pollution index, all locations are medium and high polluted. That is why the goverment, entrepreneurs, and the society should save River Telaga Waja by keeping it clean. Observation of the water quality is also should be done regularly.